Iapetus Equatorial Ridge: The Understanding from The Quran and The Hadith - Encik Ahmad Faizuddin Ramli (Tanjung Malim, 2024)
Iapetus Equatorial Ridge: The Understanding from The Quran and The Hadith by Encik Ahmad Faizuddin Ramli